Mutual antagonism between Sox10 and NFIA regulates diversification of glial lineages and glioma subtypes - Glasgow, Stacey M.; Zhu, Wenyi; Stolt, Claus; Huang, Teng-Wei; Chen, Fuyi; Loturco, Joseph J.; Neul, Jeffrey L.; Wegner, Michael; Mohila, Carrie; Deneen, Benjamin (Nature Neuroscience, 2014)
Lineage progression and diversification is regulated by the coordinated action of unique sets of transcription factors. Oligodendrocytes (OL) and astrocytes (AS) comprise the glial sub-lineages in the CNS, and the manner in which their associated regulatory factors orchestrate lineage diversification during development and disease remains an open question. Sox10 and NFIA are key transcriptional regulators of gliogenesis associated with OL and AS. We found that NFIA inhibited Sox10 induction of OL differentiation through direct association and antagonism of its function. Conversely, we found that Sox10 antagonized NFIA function and suppressed AS differentiation in mouse and chick systems. Using this developmental paradigm as a model for glioma, we found that this relationship similarly regulated the generation of glioma subtypes. Our results describe the antagonistic relationship between Sox10 and NFIA that regulates the balance of OL and AS fate during development and demonstrate for the first time, to the best of our knowledge, that the transcriptional processes governing glial sub-lineage diversification oversee the generation of glioma subtypes.
EVALuna2:4965